Evaluation of sustainability indices and indicators in the Paphos district area in Cyprus - Italos, Chrysostomos; Akylas, Evangelos; Karidis, Demetris; Hadjimitsis, Diofantos G. (My University, 2014)
During the last decades most of the coastal zones across the Mediterranean Sea concentrates population around polescities owing to the mass movement of people from the rural areas to urban areas. The extensive tourism development across the coast generates demand of new work positions and pressurizes the environment. The economic development increase the natural capital of the study areas increase the covered with buildings and infrastructures areas and as a consequence reduce the quality of life. All the above effects modify the density of the buildings and infrastructures, push and eliminate the free green covered areas and other open spaces. In order to measure the effects on the environment and the quality of life a composite index is developed which arises using combined indices using economical, social and environmental criteria. The above components give a realistic indicator of the effects on the environment. This unique index arises as a function of the ratios of a per capital income a ratio of cover area by the uncovered area and the density of people per unit area. Usually when the wealth is increased the demand of energy and goods also increased and the damage on environment becomes bigger. This paper explores how the application of sustainability indices can be used as a tool to assess the quality of life. The use of GIS and remote sensing is highlighted to support the application of the existing sustainability indices.
Keywords: Environmental effects; Environmental planning; Indicators; Land cover; Quality of life; Sustainability index; Sustainable development; Urban sprawl